Matching-up modularity methodology application within the built environment: a bibliometric review - Peter Adekunle; Clinton Aigbavboa; Kenneth Otasowie; Opeoluwa Akinradewo (Journal of Asian Architecture and Building Engineering, 2025)
Over the past several years, modularity methodology has drawn a lot of attention in the built environment and become a key area of emphasis for the construction sector. By disassembling a structure into standardised, prefabricated parts or modules that may be produced off-site and then assembled on-site, modularity is a construction technique. In order to identify possible research gaps for future studies, this study attempts to evaluate the research studies carried out on modularity technique in the built environment domain. The study also seeks to extract information from present research domain. The SCOPUS database was thoroughly searched for papers pertaining to modularity technique in the built environment using a scientometric review. Research articles from 2019 to 2024 were included in the study, which provided important insights into the themes and developments in the field of modularity methodology. The results showed that modularity technique is becoming more popular, as seen by the large number of publications in 2019. Interestingly, the study found a research gap and very little cooperation with other new developments in the built environment, like digital twins, novel materials, maximising land use, and circular economies. Cluster analysis revealed that the majority of research in this area focuses on the modularity methodology’s component parts, with little investigation into real-world applications across a range of disciplines. The study’s practical implications highlight the necessity for academics, practitioners, and policymakers in the construction sector to take modularity methodology into consideration as a workable and revolutionary strategy.